2017
DOI: 10.5539/mas.v11n10p23
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Mapping of Soil Properties Using Geostatistical Methods in the Ghazvin Plains of Iran

Abstract: Geostatistical interpolation is widely used to map spatial variability in physical and chemical properties of soil, such as organic matter content, particle density; and pH. Geostatistical interpolation is a branch of applied science which predicts spatial concentrations at unknown locations at a study area by incorporating limited measured data, which is a major advantage over classical statistics. Although many studies applied geostatistical interpolation in agricultural land, there are still gaps in knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…However, for other soil properties (pH, bulk density, cation exchange capacity, organic carbon content, volumetric moisture content (VMC) at 0.33 and 15 bars level) Empirical Bayesian Kriging showed lowest RMSE. Similar studies also have shown that Kriging method is superior for univariate soil chemical property mapping [ 10 , 11 ]. Due to sparse nature of the dataset smooth circular neighbourhood selection method was selected for pH.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 83%
“…However, for other soil properties (pH, bulk density, cation exchange capacity, organic carbon content, volumetric moisture content (VMC) at 0.33 and 15 bars level) Empirical Bayesian Kriging showed lowest RMSE. Similar studies also have shown that Kriging method is superior for univariate soil chemical property mapping [ 10 , 11 ]. Due to sparse nature of the dataset smooth circular neighbourhood selection method was selected for pH.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 83%
“…3.5 Subgrade soil map of the study area on ArcGIS platform Results of the subgrade soil properties were mapped to present the futuristic importance for geotechnical studies, investigations, design and constructions of road pavement (Eric et al, 2010;Grunwald et al, 2011;Mary and Amani, 2013;Bostani et al, 2017) of the road section found in Chencha to Ezo towns. ArcGIS software was used to prepare subgrade soil properties result maps for this study through integrated approach of the actual investigated behaviors of soils along the road stretch.…”
Section: California Bearing Ratio Resultsmentioning
confidence: 99%
“…The systematic unaligned grid (300 × 500 m) sampling method was used to collect 2652 (Figure 2) samples from 0‐ to 30‐cm depth (Mohamed & Abdo, 2011). Soil pH was measured in a 1:2.5 soil:water (distilled‐water) suspension using (VWR pHenomenal‐MU6100H meter with measurement error ± 0.002) equipped with a calibrated combined glass electrode (Bostani et al., 2017). The longitude and latitude of the data points were determined using the global positioning system (GPS) (5‐m precision).…”
Section: Methodsmentioning
confidence: 99%